How to write a poem - Ryan, Margaret (New York : F. Watts, 1996)
Explores the steps and processes involved in writing poetry, including finding subjects, rhyme and meter, free verse, making revisions, and publication.
Includes bibliographical references (p. 179-181) and index.
Booklist.
School Library Journal.
Wilson's Senior High School.
Young Adult
Keywords: Poetry -- Authorship; Poetics